2021
DOI: 10.1080/21870764.2021.1913865
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cr3+ doping on the defect characteristics and magnetic order in the CuFe1-xCrxO2 ceramics

Abstract: The defect characteristic and magnetic properties of CuFe 1-x Cr x O 2 (x = 0.0-0.4) compounds have been investigated in detail. The results demonstrate that Cr 3+ ions enter into the CuFeO 2 lattice sites and induce local lattice contraction but do not change the valance state of Cu + and Fe 3+ ions. We calculate the positron annihilation lifetime in the bulk and vacancy defect trapping states by the atomic superposition method in 3 × 3 × 1 CuFeO 2 super-cell. Combined with theoretical calculation results, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Even if defects in delafossites, in general, and CuFeO2, in particular, have not been extensively studied, it is known that antisite defects, interstitial oxygen, and vacancies are major contributors. [ 34–36 ] Besides, in a study on CuAlO 2 significant off‐stoichiometries of all constituents were reported after hydrothermal synthesis. [ 34 ] The low formation energy of antisite defects, i.e., Cu on the Fe site, in CuFeO2 [ 35 ] might thus render those defects to be intrinsic antagonists to Mn doping.…”
Section: Resultsmentioning
confidence: 99%
“…Even if defects in delafossites, in general, and CuFeO2, in particular, have not been extensively studied, it is known that antisite defects, interstitial oxygen, and vacancies are major contributors. [ 34–36 ] Besides, in a study on CuAlO 2 significant off‐stoichiometries of all constituents were reported after hydrothermal synthesis. [ 34 ] The low formation energy of antisite defects, i.e., Cu on the Fe site, in CuFeO2 [ 35 ] might thus render those defects to be intrinsic antagonists to Mn doping.…”
Section: Resultsmentioning
confidence: 99%